Attention deficit/hyperactivity disorder (ADHD) dimensions mediate the relationship between adverse childhood experiences and adult aggression depending on cognitive reappraisal - Steffen Barra; Paulina Klaudia Machalica; Petra Retz-Junginger; Johannes Merscher; Anselm Crombach; Wolfgang Retz (Scientific Reports)
Abstract Associations between adverse childhood experiences (ACEs) and aggressive behavior have often been demonstrated, but the mechanisms underneath these relations are yet unclear. As high levels of ACEs and aggression have been found among individuals with attention deficit/hyperactivity disorder (ADHD), ADHD dimensions might explain this association. Moreover, maladaptive emotion regulation is common in ADHD and was associated with aggressive behavior. The present study investigated the dynamics among these constructs in a mixed sample of 287 adults. We found partially mediating effects of current ADHD on the associations of ACEs with adult aggression, especially regarding the hyperactive/impulsive dimension. Cognitive reappraisal moderated the indirect effect between hyperactivity/impulsivity and aggression, especially for females. Hence, the unfavourable dynamics found in the present study might explain the increased risk for aggressive behavior in individuals affected by both, ACEs and ADHD. Respective gender-sensitive prevention and treatment for aggressive behavior should include adequate pharmacological and psychological approaches that address ADHD core symptoms, whilst also aiming to improve emotion regulation techniques.